2017
DOI: 10.1186/s12898-017-0124-1
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal transplants support a plasticity-first scenario during colonisation of a large hyposaline basin by a marine macro alga

Abstract: BackgroundEstablishing populations in ecologically marginal habitats may require substantial phenotypic changes that come about through phenotypic plasticity, local adaptation, or both. West-Eberhard’s “plasticity-first” model suggests that plasticity allows for rapid colonisation of a new environment, followed by directional selection that develops local adaptation. Two predictions from this model are that (i) individuals of the original population have high enough plasticity to survive and reproduce in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…In addition, a closely related species F. radicans has evolved as an endemic species from F. vesiculosus inside the Baltic Sea (Ardehed et al., ; Bergström et al., ; Pereyra et al., ). Although genomic information about geographical differences in adaptive loci is lacking, there are indications of trait differences that suggest the presence of locally adapted populations along the Baltic Sea gradient in both these species (Johansson et al., ; Pearson, Kautsky, & Serrão, ; Serrão et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a closely related species F. radicans has evolved as an endemic species from F. vesiculosus inside the Baltic Sea (Ardehed et al., ; Bergström et al., ; Pereyra et al., ). Although genomic information about geographical differences in adaptive loci is lacking, there are indications of trait differences that suggest the presence of locally adapted populations along the Baltic Sea gradient in both these species (Johansson et al., ; Pearson, Kautsky, & Serrão, ; Serrão et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Fucus vesiculosus may disperse in several ways including short‐distance dispersal of gametes and zygotes to occasional long‐distance dispersal of dislodged and rafting buoyant sexually mature plants (Rothäusler, Corell, & Jormalainen, ; Thiel & Gutow, ). Also, dispersal on intermediate scales may occur through bed load transport of negatively buoyant plants and in some cases vegetative, adventitious branches (Johansson et al., ; Pereyra et al., ). Genetic studies indicate population structure on scales ranging from, in the extreme case 10 m, but more usually 1 km, which suggest relatively short dispersal distances (Muhlin, Engel, Stessel, Weatherbee, & Brawley, ; Tatarenkov, Jonsson, Kautsky, & Johannesson, ).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study of Fucus radicans showed that this species grows better in the salinity of its current northern distributional range (4) than in the salinity of the Baltic Sea entrance (24), and the authors also reported variation in growth rate among ramets of the same clone (Johansson et al. ). Together with our results, this indicates that F. radicans is capable of phenotypic plasticity in growth with respect to salinity stress.…”
Section: Discussionmentioning
confidence: 95%
“…This has been proposed as an example of the so‐called plasticity‐first scenario for the establishment of a population in marginal habitats (Johansson et al. ). Furthermore, Baltic Sea fucoids have been shown to be phenotypically plastic for a number of other traits, such as phlorotannin production (Koivikko ), morphology (Sideman and Mathieson , Scott et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation